148k views
5 votes
When simplifying 4x^3-10x^2+6x over 2x^3+x^2-3x, what are the term(s) that can be cancelled

User RDK
by
4.0k points

1 Answer

3 votes

Answer:

Cancelling x and (2x-3), we get, the simplest form as


(4x^3-10x^2+6x)/(2x^3+x^2-3x)=(2(x-1))/((x+1))

Explanation:

Consider the given two expressions
4x^3-10x^2+6x and
2x^3+x^2-3x.

We solve both expressions seperately,

Consider the first expression
4x^3-10x^2+6x

Taking x common from the expression,


4x^3-10x^2+6x=x(4x^2-10x+6)

The terms in brackets is a quadratic equation, we can solve using middle term splitting method,


4x^2-10x+6

-10x can be written as -4x-6x , we get,


4x^2-10x+6=4x^2-4x-6x+6


\Rightarrow 4x(x-1)-6(x-1)=(4x-6)(x-1)


4x^3-10x+6)=2x(2x-3)(x-1)

Consider the second term ,
2x^3+x^2-3x

Taking x common from the expression we have,


2x^3+x^2-3x=x(2x^2+x-3)

The terms in brackets is a quadratic equation, we can solve using middle term splitting method,


2x^2+x-3

x can be written as 3x-2x


2x^2+x-3=2x^2+2x-3x-3


2x^2+2x-3x-3=2x(x+1)-3(x+1)=(2x-3)(x+1)

Thus,
2x^3+x^2-3x=x(2x-3)(x+1)

Our expression is
4x^3-10x^2+6x over
2x^3+x^2-3x

is
(4x^3-10x^2+6x)/(2x^3+x^2-3x)


(4x^3-10x^2+6x)/(2x^3+x^2-3x)=(2x(2x-3)(x-1))/(x(2x-3)(x+1))


Cancelling same terms from numerator and denominator , thus cancelling x and (2x-3), we get, the simplest form as


(4x^3-10x^2+6x)/(2x^3+x^2-3x)=(2(x-1))/((x+1))


User Laurence Mommers
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.